ANÁLISE DO COMPORTAMENTO ESTRUTURAL DE UM SISTEMA MISTO DE AÇO E CONCRETO PARA PAREDE DE CONTENÇÃO DE TALUDES - Pereira, Elvis Max (2021)
Over the years, several forms of earth retaining wall have been developed, but the search for optimization of existing ones and development of new ones that bring more efficiently to each situation is still sought. One of these retaining wall systems is the soldier pile, consisting of nailed steel profiles into the soil spaced apart and joined by timber lagging or reinforced concrete that are responsible for distributing the loads from the earth to the profiles. Taking into consideration this retaining wall structure, associated with the fact that in the case of structures using steel and concrete, the composite system concrete-steel bring advantages from of these materials union, a change was proposed to the existing soldier pile retaining wall system, so that the structure works as steel-concrete composite system. This makes the structure to resist the stresses jointly, taking advantage of the compressive strength of concrete and tensile strength of the steel. For ease of execution, the reinforced concrete lagging is partially precast, thereby reducing formwork during concreting. A calculation roadmap was developed to design the proposed system. This study aims to analyze numerically through the finite element method the structural behavior of the composite retaining wall using the ANSYS software. In order to verify the structural viability of the retaining wall analyzed in this work, a comparison of strength was made between the existing system of embedded metal profiles and the proposed system. This research seeks to present a new possibility of earth retaining wall, providing the technical environment with a modern structure, where several concepts were employed in the search for efficiency, innovation and application of a system in an area still little studied.